2020
DOI: 10.1038/s41598-020-75346-5
|View full text |Cite
|
Sign up to set email alerts
|

A variable structure pneumatic soft robot

Abstract: In this paper, a variable structure pneumatic soft robot is proposed. Its structure is variable in that when it grasps irregular objects, it can adapt to different sizes by active expansion or contraction. Its expansion range is from diameter 200 to 300 mm, its four soft pneumatic actuators (SPAs) can be rotated independently to adapt to different shapes, and it has high flexibility. The active compliant grasping method enables it to capture at the best position, which can improve the success rate of capture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Note that in Scenario B there is only one set of actuation forces (f a,left = f a,right = 1.0), namely a set of forces specifically geared for pulling the object toward the palm. We computed (13) for each grasper in Scenario A and compared the best design to that for Scenario B, for a given object in O.…”
Section: B Manipulation Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in Scenario B there is only one set of actuation forces (f a,left = f a,right = 1.0), namely a set of forces specifically geared for pulling the object toward the palm. We computed (13) for each grasper in Scenario A and compared the best design to that for Scenario B, for a given object in O.…”
Section: B Manipulation Metricmentioning
confidence: 99%
“…A vacuum actuated palm allowed the grasper to cage objects of various sizes and achieve favorable contact points on irregular objects [12]. Other graspers have featured fingers that could slide toward and away from the center of the palm, effectively changing the palm width in order to grasp a variety of object sizes [13], [14]. Variable transmission ratios, which relate the actuation torque to joint torques, are also paramount; secure power grasps can be achieved by varying the transmission ratio as the pulley radii change [15], and force isotropy can be maintained throughout a grasping sequence given certain contact locations [16].…”
Section: Introductionmentioning
confidence: 99%
“…Fluid‐driven soft manipulator: (a) PneuArm (Sanan, 2013), (b) OctArm (Mcmahan et al, 2006), (c) HPN (Jiang et al, 2016), (d) BHA (Mahl et al, 2014), (e) underwater soft manipulator (Gong et al, 2021), (f) multimodule (Cianchetti, Ranzani, et al, 2014), (g) fluidic elastomer (Marchese et al, 2015), (h) pressure‐driven lengthening (Hawkes et al, 2017), (i) omnidirectional bending (H. Dong, 2016), (j) soft robots consisting of dual‐morphing M‐ori (W. Kim, Byun, et al, 2019), (k) helical contractile PAMs (Guan et al, 2020), (l) flexible hybrid pneumatic actuator (X. Liu et al, 2021), (m) spring reinforced actuator (Fu et al, 2020), (n) a soft parallel robot (Y. Wang & Xu, 2021), (o) Octobot (Wehner et al, 2016), (p) soft hydraulic robot (Zatopa et al, 2018), (q) soft‐legged untethered quadruped robot (Drotman et al, 2021), (r) inflatable humanoid robot named King Louie (Best et al, 2021), (s) a variable structure pneumatic soft robot (W. Huang et al, 2020), (t) multisegment soft robotic fingers (Teeple et al, 2020), (u) underwater robotic manipulator (Shen et al, 2020), (v) nanofiber‐reinforced soft robotic actuators (Sinatra et al, 2019), (w) fabric‐based versatile and stiffness‐tunable soft gripper (Fei et al, 2019), (x) three‐finger soft pneumatic gripper (Tawk et al, 2018), (y) soft pneumatic microactuators (Konishi & Hirata, 2019), (z) robotic continuum manipulator driven by pMA (Kang et al, 2013) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Research Status Of Soft Manipulatormentioning
confidence: 99%
“…Killpack et al (Best et al, 2021) designed and developed an inflatable humanoid robot named King Louie, who had two pneumatic soft arms, as shown in Figure 3r. W. Huang et al (2020) proposed a variable structure pneumatic soft robot, whose structure was variable in that when it grasped irregular objects, it could adapt to different sizes by active expansion or contraction, as shown in Figure 3s. Teeple et al (2020) designed soft robotic fingers for robust precision grasping, as shown in Figure 3t.…”
Section: Fluid-driven Modementioning
confidence: 99%
“…The gripping posture can be increased by increasing the number of the finger. By rotating the four fingers and changing the distance between the fingers, the gripping posture and size of the soft gripper could be continuously adjusted to grip objects of different shapes, postures and sizes (Huang et al , 2020). However, the rotation of the four fingers is controlled by four servos, which enormously increases the structure and control complexity of the gripper.…”
Section: Introductionmentioning
confidence: 99%